2004
DOI: 10.1007/s00415-004-0317-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in patients with Guillain-Barr� syndrome (GBS)

Abstract: The possible relationship between Guillain-Barré syndrome (GBS) and cancer is still controversial and the existence of a paraneoplastic GBS remains unconfirmed. To better define whether there is a relationship between GBS and malignancy, we compared the observed and the expected number of patients with tumours in a population-based cohort of subjects with GBS. Clinical differences between GBS patients with or without malignancies were analysed. Data were obtained from the Piemonte and Valle d'Aosta Register fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 19 publications
1
48
0
2
Order By: Relevance
“…Some reports have supported the possible correlation between GBS and cancer (14,15), and it is hypothesized that the pathophysiology is due to antibodies derived from the molecular mimicry of antigens in lymphoma cells which may attack similar antigens in the peripheral nerve cells (1). Among the patients which were listed in Table, Noguchi et al demonstrated that their patient's B cell lymphoma produced a monoclonal IgM autoantibody against glycolipids GM1 and GD1b, which caused multifocal motor neuropathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have supported the possible correlation between GBS and cancer (14,15), and it is hypothesized that the pathophysiology is due to antibodies derived from the molecular mimicry of antigens in lymphoma cells which may attack similar antigens in the peripheral nerve cells (1). Among the patients which were listed in Table, Noguchi et al demonstrated that their patient's B cell lymphoma produced a monoclonal IgM autoantibody against glycolipids GM1 and GD1b, which caused multifocal motor neuropathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Ig. There is some evidence suggesting that patients with GBS and cancer have a worse neurologic outcome than those without cancer [95].…”
Section: Subacute Sensory Neuronopathymentioning
confidence: 99%
“…Patients with Hodgkin lymphoma are at increased risk of developing an acute polyradiculoneuritis identical to Guillain-Barré syndrome (GBS) [44]. In some patients, the GBS may be the first manifestation of tumor relapse.…”
Section: Polyradiculoneuritis (Guillain-barré) and Brachial Neuritismentioning
confidence: 99%
“…In some patients, the GBS may be the first manifestation of tumor relapse. Treatment is the same as for the non-cancer related forms of GBS and consists of plasma exchange and IVIg neither of which is contraindicated in patients with cancer [44]. There is some evidence suggesting that patients with cancer-associated GBS have a worse neurological outcome compared to patients with GBS and no underlying cancer [44].…”
Section: Polyradiculoneuritis (Guillain-barré) and Brachial Neuritismentioning
confidence: 99%